PERILAKU LENTUR BALOK-L BETON BERTULANG BERLUBANG DITINJAU SECARA EKSPERIMEN DAN ANALISIS NUMERIK MEMAKAI SOFTWARE GID-ATENA - Kori Effendi, Mahmud (Semarang State University, 2010)
Abstract:.Investigation on behavior of openings-beam reinforced concrete with the variation type of sidedÃÂ is ÃÂ conductedÃÂ experimentallyÃÂ andÃÂ numericalÃÂ analyticallyÃÂ usingÃÂ GID-ATENAÃÂ software.ÃÂ Used specimensÃÂ wereÃÂ reinforcedÃÂ concreteÃÂ L-shapedÃÂ beamÃÂ designedÃÂ withÃÂ ultimateÃÂ loadÃÂ 2600ÃÂ NÃÂ and having tension reinforcement 2D13 with roll and hinge support. Beam had 2 m span, 150 mm web width, 250 mm high, effective 317 mm width and slab 100 mmÃÂ thick,. To differentiate behavior of openings, a specimen without openings ( BLK01), a specimen with openings 100 mm x 100 mm ( BLKLB01), a specimen with openings 200 mm x 100 mm ( BLKLB02) were made. An opening was 150 mmÃÂ fromÃÂ right support. Pure moment was done withÃÂ load 650 mmÃÂ from support. To compare experiment,ÃÂ 3DÃÂ modelÃÂ GID-ATENAÃÂ wasÃÂ analyzed.ÃÂ TheÃÂ materialÃÂ modelÃÂ ofÃÂ concreteÃÂ was CCCOMBINEDMATERIALÃÂ andÃÂ CC1DELASTLSOTROPICÃÂ forÃÂ reinforcement.ÃÂ ThisÃÂ analysisÃÂ used geometricÃÂ and materialÃÂ nonÃÂ linearÃÂ analyses.ResultÃÂ of GID-ATENAÃÂ analysisÃÂ indicateÃÂ thatÃÂ theÃÂ first crack load were less than 42-62 %, ultimate load were less than 33-47%, mid-span displacement at first crack load were less than 55-86%, and mid-span displacement at ultimate load were less than 45-70% comparedÃÂ toÃÂ the experimentÃÂ result. First crack pattern of BLK01 occuredÃÂ inÃÂ the mid-span whileÃÂ BLKLB01ÃÂ andÃÂ BLKLB02ÃÂ occurredÃÂ belowÃÂ theÃÂ hole. ResultÃÂ ofÃÂ analysis GID-ATENAÃÂ getÃÂ the different result of its first crack pattern. Keywords: openings-beam, L-shaped beam, GID-ATENA ÃÂ Abstrak:ÃÂ PengamatanÃÂ perilakuÃÂ balokÃÂ betonÃÂ bertulangÃÂ berlubangÃÂ diÃÂ badanÃÂ denganÃÂ variasiÃÂ entuk persegi panjangÃÂ ÃÂ dilakukanÃÂ secara eksperimen. BendaÃÂ ujiÃÂ yang digunakan adalahÃÂ balokÃÂ LÃÂ beton bertulangÃÂ yangÃÂ dirancangÃÂ denganÃÂ bebanÃÂ 2600ÃÂ NÃÂ danÃÂ menghasilkanÃÂ tulanganÃÂ tunggalÃÂ 2D13 denganÃÂ tumpuan sendi danÃÂ rol. Balok mempunyai bentang 2 m,ÃÂ lebar web 150 mm,ÃÂ tinggi 250 mm, tebal slab 100 mm, lebar efektif 317 mm. Untuk mengetahui perilaku lubang di badan maka dibuatÃÂ bendaÃÂ ujiÃÂ balok ÃÂ tanpaÃÂ lubangÃÂ (BLK01),ÃÂ balokÃÂ denganÃÂ lubangÃÂ 100ÃÂ mmÃÂ xÃÂ 100ÃÂ mm (BLKLB01),ÃÂ balokÃÂ denganÃÂ lubangÃÂ 200 mmÃÂ xÃÂ 100 mmÃÂ (BLKLB02).ÃÂ JarakÃÂ lubangÃÂ 150 mmÃÂ dari tumpuan kanan. Masing2 benda uji 1 buah. Untuk mengetahui kapasitas beban maksimum yang ditahanÃÂ balok,ÃÂ balokÃÂ ditesÃÂ lentur murniÃÂ denganÃÂ jarakÃÂ bebanÃÂ titikÃÂ 650 mmÃÂ dariÃÂ tumpuan.ÃÂ Hasil analisis GID-ATENA menunjukkan bahwa beban retak balok pertama lebih kecil 42-62 %, beban ultimit balok lebih kecil 33-47%, lendutan tengah bentang pada beban retak pertama lebih kecil 55-86%,ÃÂ danÃÂ lendutanÃÂ tengahÃÂ bentangÃÂ padaÃÂ bebanÃÂ ultimitÃÂ lebihÃÂ kecilÃÂ 45-70%ÃÂ terhadapÃÂ hasil eksperimen. Pola retak pertama balok BLK01 terjadi di tengah bentang sedangkan BLKLB01 dan BLKLB02ÃÂ terjadi di bawahÃÂ lubang. Hasil analisis GID-ATENA mendapatkan hasil yang berbeda pola retak pertamanya. Kata Kunci: Balok lubang, Balok L, GID-ATENA